2021
DOI: 10.2967/jnumed.120.258434
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of 68Ga-NOTA (68Ga-NGUL) and 68Ga-PSMA-11 in Patients with Metastatic Prostate Cancer: A Prospective Study

Abstract: Ga-NOTA Glu-Urea-Lys (NGUL) is a novel prostate-specific membrane antigen (PSMA)-targeting tracer used for PET/CT imaging. This study aimed to compare performance in the detection of primary and metastatic lesions and to compare biodistribution between 68 Ga-NGUL and 68 Ga-PSMA-11 in the same patients with prostate cancer. Methods: Eleven patients with metastatic prostate cancer were prospectively recruited. The quantitative tracer uptake was determined in normal organs and in primary and metastatic lesions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
2
7
0
4
Order By: Relevance
“…Radiotracer activity in the bladder majorly contributed to effective dose, and for this reason, the effective dose was also relatively higher than that of PSMA-11 (0.025 mSv/MBq vs. 0.017 mSv/MBq). However, exposure to other organs, including the kidney (0.332 mGy/MBq vs. 0.371 mGy/MBq) and spleen (0.022 mGy/MBq vs. 0.065 mGy/MBq), was lower than that of 68 Ga-PSMA-11, which is in line with the results of a previous comparative study [ 8 ]. The lower molecular weight (769.82 g/mol vs. 947 g/mol) and higher hydrophilicity (log P = -3.3 vs. -3.9) of 68 Ga-NGUL compared with 68 Ga-PSMA-11 may explain the difference in the urinary excretion.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Radiotracer activity in the bladder majorly contributed to effective dose, and for this reason, the effective dose was also relatively higher than that of PSMA-11 (0.025 mSv/MBq vs. 0.017 mSv/MBq). However, exposure to other organs, including the kidney (0.332 mGy/MBq vs. 0.371 mGy/MBq) and spleen (0.022 mGy/MBq vs. 0.065 mGy/MBq), was lower than that of 68 Ga-PSMA-11, which is in line with the results of a previous comparative study [ 8 ]. The lower molecular weight (769.82 g/mol vs. 947 g/mol) and higher hydrophilicity (log P = -3.3 vs. -3.9) of 68 Ga-NGUL compared with 68 Ga-PSMA-11 may explain the difference in the urinary excretion.…”
Section: Discussionsupporting
confidence: 90%
“…As previously reported in a comparative study of 68 Ga-PSMA-11, rapid urinary excretion of 68 Ga-NGUL was observed [ 8 ]. Accordingly, it was estimated that the urinary bladder wall had the highest absorbed dose.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…National Comprehensive Cancer Network guideline 을 살펴보면 68 Ga-PSMA-11과 18 [17][18][19][20] 또한, 전립선외에도 침샘, 신장, 소장, 간, 비장 등 다른 장기에서 낮은 수준으로 PSMA가 발현되는 것으로 알려져 있다. 21,22 그 외에도 아직까지 정확한 이유는 밝혀 져 있지 않지만 다른 고형암들의 종양관련 신생혈관 부위 에서도 PSMA의 발현도가 높게 관찰된다.…”
unclassified
“…[23][24][25] 3. Action of PSMA-Targeted Theranostic Agent Ga-PSMA-11, 18 F-PSMA-11, 18 F-PSMA-1007, 18 F-rhPSMA 7.3, 68 Ga-PSMA-617, 68 Cu-PSMA-I&T, 44 Sc-PSMA-617 등이 전임상 및 임상 연구에 활발히 적용되기 시작하였다. 34 2.…”
unclassified